Gulf Charities and Islamic Philanthropy in the "Age of Terror" and Beyond - Benthall, Jonathan; Lacey, Robert (Berlin [Germany] : Gerlach Press, 2014)
Annotation Gulf Charities and Islamic Philanthropy in the "Age of Terror" and Beyond is the first book to be published on the charities of Saudi Arabia and the Arabian Gulf, covering their work both domestic and international. From a diversity of viewpoints, the book addresses: the historical roots of Islamic philanthropy in religious traditions and geopolitical movements; the interactions of the Gulf charities with "Western" relief and development institutions - now under pressure owing to budgetary constraints; numerous case studies from the Middle East, Africa, and South Asia; the impact of violent extremism on the sector, with the legal repercussions that have followed - especially in the USA; the recent history of attempts to alleviate the obstacles faced by bona fide Islamic charities, whose absence from major conflict zones now leaves a vacuum for extremist groups to penetrate; the prospects for a less politicized Islamic charity sector when the so-called "war on terror" eventually loses its salience.
VII. Madrasas in South Asia and Afghanistan12 The Madrasas of South Asia and their Implications for Gulf Charities; 13 Madrasas in South Asia: the Strategic Geopolitical Concern aboutGulf Charities; VIII. Charitable Activities Beyond Geopolitics; 14 Giving to Give, and Giving to Receive: the Construction ofCharity in Dubai; 15 Care, Redemption, and the Afterlife: Spiritual Experiences ofBathing Volunteers in a Charity Care Center in Iran; 16 Afterword: Capital, Migration, Intervention: Rethinking GulfIslamic Charities; Envoi "...and beyond"; About the Contributors; Index
Vendor-supplied metadata.
Includes bibliographical references and index.
Master record variable field(s) change: 072
Keywords: Charities -- Persian Gulf Region; Islam -- Charities; Islam and social problems -- Persian Gulf Region; Islam -- Social aspects -- Persian Gulf Region; POLITICAL SCIENCE / Public Policy / Social Services & Welfare; SOCIAL SCIENCE / Human Services; Charities; Islam and social problems; Islam -- Charities; Islam -- Social aspects; Middle East -- Persian Gulf Region; Charities -- Political aspects -- Middle East; Endowments -- Political aspects -- Middle East; Terrorism -- Middle East -- Finance; HISTORY / Middle East / General; Electronic books